Measures for Social Enterprise Promotion Pursuant to the Social Enterprise Promotion Act B.E. 2562 (2019) - Phumpuong, Jeera; Jongjakapun, Kumchai (Rajapark Journal, 2022)
The objectives of this research were to study 1) the meaning and importance of social enterprise or business management fundamentally aiming to address social and environmental issues advancement as well as economic development; 2) international legal procedure and foreign policy for determining social enterprise promotion measures compared to Thailand; and 3) juridical issues created by promoting social enterprises following the Social Enterprise Promotion Act B.E. 2562 (2019; The Act). In addition, pertinent recommendations were offered to amend relevant Thai law. Qualitative documentary research was done with data collected from published domestic and international articles, journals, and electronic media. Results found that The Act aimed to promote business operations by creating jobs for the underprivileged while resolving social and environmental issues and developing communities, society, the environment, and related common interests. Yet the Act did not establish any benefits legally and offered no precedents for financial compensation from funds, tax benefits, or privileges according to the Government Procurement and Inventory Management Act B.E. 2560 (2017). In addition, obstacles impeded secondary law formulation procedures. These findings suggest that The Act should be amended by supplementary legislation to reinforce social enterprise development, expand domestic and international trade, and further extend national and international trade competitiveness.